2015
DOI: 10.1097/pcc.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Dysfunction Following Brain Death in Children

Abstract: Background Cardiac dysfunction has been reported to occur in as much as 42% of adults with brain death, and may limit cardiac donation after brain death. Knowledge of the prevalence and natural course of cardiac dysfunction after brain death may help to improve screening and transplant practices but adequately sized studies in pediatric brain death are lacking. The aims of our study are to describe the prevalence and course of cardiac dysfunction after pediatric brain death. Methods We conducted a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Additionally, there was a strong correlation between increased circulatory inflammatory biomarkers and impaired LVEF (refer to Table 2). Intriguingly, a link between an increase in inflammatory biomarkers and LV dysfunction/heart failure has been clearly elucidated in settings of IS or brain damage with any etiology [28][29][30][31]. Again, our finding was comparable with the findings of previous studies [7,[28][29][30][31] regarding the complex brain-heart interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, there was a strong correlation between increased circulatory inflammatory biomarkers and impaired LVEF (refer to Table 2). Intriguingly, a link between an increase in inflammatory biomarkers and LV dysfunction/heart failure has been clearly elucidated in settings of IS or brain damage with any etiology [28][29][30][31]. Again, our finding was comparable with the findings of previous studies [7,[28][29][30][31] regarding the complex brain-heart interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Another prospective study(20) demonstrated troponin elevation in 31% of patients following moderate-severe TBI; while echocardiographic dysfunction was not demonstrated in that study, the majority of echocardiograms were performed several days after injury, a period by which most patients in our study had recovered normal systolic function. Acute systolic dysfunction has also been observed after several severe acute non-TBI neurologic diseases including acute emotional distress(21) (classic Takotsubo’s cardiomyopathy), SAH(22), ischemic stroke(23, 24), epilepsy(25, 26), and brain death(27). …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated decreased utilization of potential donor hearts with echocardiographic evidence of ejection fractions <50%, and ISHLT guidelines have similarly recommended refusal of donor hearts with ejection fractions <40% . This practice has been supported by several pediatric and adult studies suggesting higher rates of graft failure following transplant of hearts with ejection fractions <50% and a recent pediatric donor utility survey demonstrating half of all respondents would decline an otherwise acceptable organ with an ejection fraction <50% …”
Section: Donor Echocardiographic Evaluationmentioning
confidence: 99%
“…The data in pediatric and young adult populations, where CVA is clearly an uncommon cause of death, are similarly mixed. Some studies suggest that CVA as the donor cause of death is associated with slightly higher 1‐year mortality rates following transplantation, but others have not . While it is plausible that the association between donor CVA and subsequent post‐transplant mortality differs between adults and children, there is insufficient data to support this assertion.…”
Section: Donor Cause Of Deathmentioning
confidence: 99%
See 1 more Smart Citation